Understanding Hypertension Risk among Undergraduates in Ahmad Dahlan University, Indonesia: Understanding Hypertension Risk among Undergraduates in Ahmad Dahlan University, Indonesia - Safitri, Nurhikmah; Solikhah, Solikhah; Febriyanto, Kresna; Sangruangake, Monthida (Disease Prevention and Public Health Journal, 2024)
Background: Hypertension remains a serious public health issue globally, affecting almost all groups, including the younger population. The purpose of this study was to explore hypertension understanding among students at Ahmad Dahlan University, Indonesia. Method: A structured, interview-directed questionnaires, was used in this cross-sectional offline study. The study population comprised undergraduates’ students of university situated in Ahmad Dahlan University. The sample of this study amounted to 394 people through the calculation of the sample size with the Slovin approach.  Results: A total 394 participants took part in the study comprising 50 (12,69%) medical undergraduate students and 344 (87,31%) non-medical undergraduate students. The logistic regression model indicated that the logistic regression model indicated that family history (AOR = 0.190; 95% CI = 0.097 – 0.374; p-value = 0.000), alcohol consumption behaviors (AOR = 0.078; 95% CI = 0.021 – 0.287; p-value = 0.000), and stress (AOR = 0.712; 95% CI = 0.516 – 0.982; p-value = 0.038) among undergraduates are associated with hypertension. Meanwhile, age, sex, smoking, coffee drinking routines, and physical activity were indicated to have no relationship with hypertension. Conclusion: In this study, it was concluded that the risk factor of hypertension were family history, stress, and alcohol consumption. These finding highlight that focus surrounding hypertension prevention should shift toward individual risk profiling and should be tailored toward and individual’s specific needs.